2019
DOI: 10.1038/s41598-018-36917-9
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-SNAIL axis induces Müller glial-mesenchymal transition in the pathogenesis of idiopathic epiretinal membrane

Abstract: The epithelial-mesenchymal transition (EMT) is a key process in fibrogenic diseases where transdifferentiated myofibroblasts produce excessive amounts of extracellular matrix, resulting in organ dysfunction. Idiopathic epiretinal membrane (iERM) is a vision-threatening disorder characterized by fibrocellular proliferation and contraction on the central retina. Müller glial cells, which regulate retinal physiology and structure, are the major cellular components in the iERM tissue; however, the pathological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 34 publications
4
39
0
6
Order By: Relevance
“…4a). Moreover, iERM is gradually modified by the migration of Müller glial cells and cytokines such as transforming growth factor-beta from the retina, as reported previously 38 . The cell migration becomes easier when the tractional force is greater, and cytokines are reported to be concentrated in eyes with a shorter AL 39 , most probably because vitreous liquefaction has not progressed much; this slows the turnover of soluble factors 40 .…”
Section: Discussionsupporting
confidence: 76%
“…4a). Moreover, iERM is gradually modified by the migration of Müller glial cells and cytokines such as transforming growth factor-beta from the retina, as reported previously 38 . The cell migration becomes easier when the tractional force is greater, and cytokines are reported to be concentrated in eyes with a shorter AL 39 , most probably because vitreous liquefaction has not progressed much; this slows the turnover of soluble factors 40 .…”
Section: Discussionsupporting
confidence: 76%
“… 9 , 10 Interestingly, αSMA can be expressed by cells derived from retinal pigment epithelial cells and hyalocytes, respectively, after a process of epithelial-mesenchymal transition or transdifferentiation, 4 , 11 , 12 and by Müller cells 13 , 14 after a process of glial-mesenchymal transition. 15 In practice, all cell types that have been proposed to give rise to ERM cells can transdifferentiate into a myofibroblast-like phenotype because reactive astrocytes can also express αSMA. 16 …”
mentioning
confidence: 99%
“…6,7 As concerns the cellular source of myofibroblasts in epiretinal fibrocellular proliferation seen in idiopathic epiretinal membrane, we recently revealed that Müller glial cells are equipped with fibrogenic EMT program for the expression of TβR, SNAIL, and smooth muscle protein (SM)22, which would thus be termed the Müller glialmesenchymal transition (GMT) as an alternative to EMT. 9 In fibrovascular proliferation associated with PDR, however, little is yet known about the involvement of Müller GMT promoted by the TGF-β-SNAIL axis, although Müller glial cells in patient tissues were suggested to bear a contractile phenotype expressing α-smooth muscle actin (SMA). 10 It is also yet to be elucidated whether Müller glial cells have any capacity for the profibrotic TGF-β autoinduction as seen in RPE cells during subretinal fibrovascular proliferation.…”
mentioning
confidence: 99%